Edukasi Pentingnya Kesehatan Organ Reproduksi dan Personal Hygiene pada Wanita Usia Subur (WUS) di Kecamatan Pancatengah - Amsana Amsana; Syamimi Zulfana (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2023)
Introduction: women of reproductive age is a condition of a woman between the ages of 15-49 years who is naturally said to be ready to experience pregnancy. Women's reproductive health needs special attention, this is related to the condition of women who are more vulnerable to reproductive health problems, including women of reproductive age with a history or currently using contraceptives, maintaining the hygiene of the reproductive organs in women of reproductive age, and women of reproductive age ignorance of the problem of Sexually Transmitted Infections (STIs). Reproductive organ care can automatically be carried out by doing personal hygiene regularly. Objective: The purpose of this Community Service is to increase the knowledge of women of reproductive age about Reproductive Organ Health and Personal Hygiene. Method: The method used was education with the help of a flip sheet on Reproductive Organ Health and Personal Hygiene to 100 women of reproductive age in Kp. Sempur Ds. Neglasari Kec. Pancatengah Kab. Tasikmalaya with pre test and post test as the evaluation method. Result: The result of this Community Service activity is an increase in knowledge both from the pre-test results of 25% to 85% post-test results reproductive organ health and personal hygiene. Conclusion: There was an increase in knowledge of women of reproductive age about reproductive health and personal hygiene.